2017
DOI: 10.1002/maco.201709761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on corrosion behavior of 316L stainless steel in hydrogenated high temperature water

Abstract: The effect of pH on the corrosion behavior of 316L stainless steel (SS) was investigated. The film resistance decreases and the corrosion current density increases as the pH rises from 6.42 to 7.52 for 316L SS. The corrosion rate of 316L SS increases with increasing pH in hydrogenated high temperature water at 300 °C. Higher pH reduces the stability of the oxide films and accelerates the dissolution process of the oxides. It is recommended that a proper lower pH in hydrogenated high temperature water can mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The construction model of such EEC is consistent with the interface structure of the oxide film observed by STEM. [23] T A B L E 3 The position of characteristic peaks for the oxide films formed on the RASP-treated 316LN SS specimens As shown in Figure 8a, the low-frequency regions of these Nyquist diagrams are composed of irregular arcs corresponding to the inner layer of the oxide films. The inner layer plays a leading role in corrosion resistance.…”
Section: Eis Resultsmentioning
confidence: 99%
“…The construction model of such EEC is consistent with the interface structure of the oxide film observed by STEM. [23] T A B L E 3 The position of characteristic peaks for the oxide films formed on the RASP-treated 316LN SS specimens As shown in Figure 8a, the low-frequency regions of these Nyquist diagrams are composed of irregular arcs corresponding to the inner layer of the oxide films. The inner layer plays a leading role in corrosion resistance.…”
Section: Eis Resultsmentioning
confidence: 99%
“…Similar to usual electrochemical measurements, a cell with three electrodes is needed for HTHP measurements (Figure 5), where the working electrode is the electrode studied. The HTHP counter electrode is usually platinum, [59,73,77] although platinum-coated niobium, [64,71] alumina ceramic with platinum powder, [62] titaniumbased material [24,63,80] as well as autoclave body [81] were also reported as the auxiliary electrode. The HTHP reference electrode is, in general, a pressure-balanced silver/silver chloride electrode [17,24,59,[62][63][64]73,77,80,82] filled with potassium chloride.…”
Section: Hthp Electrochemical Measurements-experimental Protocolmentioning
confidence: 99%
“…The HTHP counter electrode is usually platinum, [59,73,77] although platinum-coated niobium, [64,71] alumina ceramic with platinum powder, [62] titaniumbased material [24,63,80] as well as autoclave body [81] were also reported as the auxiliary electrode. The HTHP reference electrode is, in general, a pressure-balanced silver/silver chloride electrode [17,24,59,[62][63][64]73,77,80,82] filled with potassium chloride. Marginally, zirconium/zirconium oxide [71] and nickel-chromium-molybdenum alloy [81] were also used as reference electrodes, since some issues with silver/silver chloride reference were reported under very high pressure (17 MPa) [81] and given that solution contamination might occur with pressurebalanced references during experiments lasting several days.…”
Section: Hthp Electrochemical Measurements-experimental Protocolmentioning
confidence: 99%
“…The previous report has indicated that environmental pH has significant effect on the corrosion of materials not only in the abiotic environment [11][12][13][14][15], but also in the microbial environment [16][17][18]. However, the recent literature has focused mostly on MIC behaviour of duplex stainless steel at a neutral pH [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%